Retinoic Acid Receptor α Fusion to PML Affects Its Transcriptional and Chromatin-Remodeling Properties - Segalla, Simona (American Society for Microbiology, 2003)
PML-RAR is an oncogenic transcription factor forming in acute promyelocytic leukemias (APL) because of a chromosomal translocation. Without its ligand, retinoic acid (RA), PML-RAR functions as a constitutive transcriptional repressor, abnormally associating with the corepressor-histone deacetylase complex and blocking hematopoietic differentiation. In the presence of pharmacological concentrations of RA, PML-RAR activates transcription and stimulates differentiation. Even though it has been suggested that chromatin alteration is important for APL onset, the PML-RAR effect on chromatin of target promoters has not been investigated. Taking advantage of the Xenopus oocyte system, we compared the wild-type transcription factor RARα with PML-RAR as both transcriptional regulators and chromatin structure modifiers. Without RA, we found that PML-RAR is a more potent transcriptional repressor that does not require the cofactor RXR and produces a closed chromatin configuration. Surprisingly, repression by PML-RAR occurs through a further pathway that is independent of nucleosome deposition and histone deacetylation. In the presence of RA, PML-RAR is a less efficient transcriptional activator that is unable to modify the DNA nucleoprotein structure. We propose that PML-RAR, aside from its ability to recruit aberrant quantities of histone deacetylase complexes, has acquired additional repressive mechanisms and lost important activating functions; the comprehension of these mechanisms might reveal novel targets for antileukemic intervention.